Economic Analyses and Accounting Techniques: Perspective and Proposals - Gonedes, Nicholas J.; Dopuch, Nicholas (Journal of Accounting Research, 1979)
Accounting techniques, Earnings, Firm performance, Systematic properties of accounting numbers